OPTIMIZING ZIS FUND DISTRIBUTION THROUGH THE DAI TANGGUH PROGRAM: A CASE STUDY AT LAZNAS BAITUL MAAL HIDAYATULLAH - Muharrik Fitragara Fachreza; Yayat Sujatna (Jurnal Media Akademik (JMA), 2026)
This study analyzes the optimization of the distribution mechanism and the gap between the collection and distribution of Zakat, Infak, and Sedekah (ZIS) funds through the Dai Tangguh Program at LAZNAS BMH, as well as the supporting and inhibiting factors. The issue that arises is that not all Dai Tangguh receive kafalah from BMH. The research method uses a mixed method, with primary data obtained through semi-structured interviews with BMH and Dai Tangguh representatives, and supported by secondary data from BMH's Annual Reports for 2022–2024. Validity is ensured through triangulation analysis. The research findings indicate that data from 2022–2024 show an average gap of 4.71% between the total ZIS collected and distributed, with the largest discrepancy occurring in 2023 at 8.56%. Fund allocation to the Dai Tangguh Program also varies, averaging 2.42% of total ZIS and 7.53% of dakwah funds, with Dai Tangguh funds increasing by 36.29% in 2023 and decreasing by 16.19% in 2024. Recommendations include strengthening the KPI Maqashid Shariah-based monitoring and evaluation system, developing public communication strategies, and improving human resource capacity and digital infrastructure. The implementation of periodic field audits and geographical risk mapping is expected to minimize inaccuracies in targeting and improve accountability. These findings contribute to Islamic philanthropy management practices and can serve as a blueprint for other zakat institutions in optimizing ZIS fund distribution.